Pyrolysis of Sugarcane (Saccharum officinarum L.) Leaves and Characterization of Products - Kumar, Mohit; Upadhyay, Siddh Nath; Mishra, P.K. (American Chemical Society, 2022)
The finite nature, regional availability, and environmental problems associated with the use of fossil fuels have forced all countries of the world to look for renewable eco-friendly alternatives. Agricultural waste biomasses, generated through the cultivation of cereal and noncereal crops, are being considered renewable and viable alternatives to fossil fuels. In view of this, there has been a global spurt in research efforts for using abundantly available agricultural wastes as feedstocks for obtaining energy and value-added products through biochemical and thermal conversion routes. In the present work, the thermochemical characteristics and thermal degradation behavior of sugarcane leaves (SCL) and tops were studied. The batch pyrolysis was carried out in a fixed-bed tubular reactor to obtain biochar, bio-oil, and pyrolytic gas. Effects of bed height (4-16 cm), particle size (0.180-0.710 mm), heating rate (15-30 °C/min), and temperature (350-650 °C) were investigated. The maximum yields of bio-oil (44.7%), biogas (36.67%), and biochar (36.82%) were obtained at 550, 650, and 350 °C, respectively, for a 16 cm deep bed of particles of size 0.18-0.30 mm at the heating rate of 25 °C/min. The composition of bio-oil was analyzed using Fourier transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance (1H NMR), and gas chromatography-mass spectrometry (GC-MS) techniques. Several aliphatic, aromatic, phenolic, ketonic, and other acidic compounds were found in the bio-oil. The biochar had a highly porous structure and several micronutrients, making it useful as a soil conditioner. In the middle temperature ranges, biogas had more methane and CO and less hydrogen, but at higher temperatures, hydrogen was predominant.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Reaxys Chemistry database information